2020
DOI: 10.1523/jneurosci.0617-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Oscillatory Dynamics Underlie Different Components of Hierarchical Cognitive Control

Abstract: Hierarchical cognitive control enables us to execute actions guided by abstract goals. Previous research has suggested that neuronal oscillations at different frequency bands are associated with top-down cognitive control, however, whether distinct neural oscillations have similar or different functions for cognitive control is not well understood. The aim of the current study was to investigate the oscillatory neuronal mechanisms underlying two distinct components of hierarchical cognitive control: the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 66 publications
(80 reference statements)
1
17
1
1
Order By: Relevance
“…The present study focused on reactive control during sensory and motor interference. Accordingly, our results cannot rule out that increases in midfrontal theta power can also occur in other behavioral task contexts (Hsieh and Ranganath, 2014;Kaiser et al, 2021;Riddle et al, 2020). Recent studies have found evidence that different neural generators project theta activity on the midfrontal cortex (Töllner et al, 2017;Zuure et al, 2020).…”
Section: Discussioncontrasting
confidence: 56%
“…The present study focused on reactive control during sensory and motor interference. Accordingly, our results cannot rule out that increases in midfrontal theta power can also occur in other behavioral task contexts (Hsieh and Ranganath, 2014;Kaiser et al, 2021;Riddle et al, 2020). Recent studies have found evidence that different neural generators project theta activity on the midfrontal cortex (Töllner et al, 2017;Zuure et al, 2020).…”
Section: Discussioncontrasting
confidence: 56%
“…As described above, posterior theta-band power may shift into alpha frequency as the dominant posterior oscillation ( Rodríguez-Martínez et al, 2017 ), while a frontal theta oscillation may mature separately during development ( Adam et al, 2020 ; Barriga-Paulino et al, 2011 ). This relatively late emergence of intrinsic, frontal-midline theta oscillation may be related to the development of cognitive functions known to recruit frontal-midline theta oscillations, for example feedback and error processing ( Cavanagh and Frank, 2014 ; Nigbur et al, 2011 ; Velanova et al, 2008 ) and hierarchical cognitive control ( Riddle et al, 2020c ; Unger et al, 2016 ). Specifically, many cognitive functions, for example working memory and top-down control are known to have a protracted development through adolescence ( Luna et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our follow-up analysis utilized the modulation index to normalize differences in magnitude of left frontal alpha oscillations across patients. Multiple comparisons were reduced by pre-registering our primary outcome, focusing on a single region of interest, defining a single time-frequency cluster from all trials in the emotional valence task (permutation-based cluster correction for mass [25]), and focusing on positive valence [3]. Exploratory analyses include topographic analysis with a significance threshold of three significant contiguous electrodes, individual differences analysis using depression severity, IAF-tACS effect as a function of antidepressant use, the relationship of IAF functional connectivity between left and right prefrontal cortex to depression severity, and the impact of IAF-tACS in healthy control participants.…”
Section: Discussionmentioning
confidence: 99%